Advice on tackling cannabis education. (2nd October 2022) - Conibear, Helena
Abstract : Use of cannabis among teenagers is on the rise and charity the Alcohol Education Trust has responded with new workshops for schools. CEO Helena Conibear offers some tips on tackling cannabis education